2004
DOI: 10.1021/tx0342060
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Urinary Excretion of Arsenic Triglutathione and Methylarsenic Diglutathione

Abstract: Taking advantage of mice deficient in gamma-glutamyl transpeptidase that are unable to metabolize glutathione (GSH), we have identified two previously unrecognized urinary metabolites of arsenite: arsenic triglutathione and methylarsenic diglutathione. Following administration of sodium arsenite to these mice, approximately 60-70% of urinary arsenic is present as one of these GSH conjugates. We did not detect the dimethyl derivative, dimethyl arsenic GSH; however, dimethyl arsenic (DMAV) represented approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 39 publications
1
76
0
Order By: Relevance
“…The authors suggested that the redundancy of transmembrane export pumps offers equivalent protection to the Mrp1(Ϫ/Ϫ) animals as the Mrp1(ϩ/ϩ) mice (62,63). An independent investigation of Mrp1(Ϫ/Ϫ) mice from the same colony revealed that 1 h after injection of As III there were no differences in urinary excretion of As III between Mrp1(ϩ/ϩ) and Mrp1(Ϫ/Ϫ) mice, suggesting that Mrp1 is not critical to urinary excretion of arsenic (28). In sharp contrast to the short exposure times and relatively high doses of arsenic used in these animal studies (28,62,63), human tumor formation is associated with long term exposure to comparatively low doses of arsenic (14).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The authors suggested that the redundancy of transmembrane export pumps offers equivalent protection to the Mrp1(Ϫ/Ϫ) animals as the Mrp1(ϩ/ϩ) mice (62,63). An independent investigation of Mrp1(Ϫ/Ϫ) mice from the same colony revealed that 1 h after injection of As III there were no differences in urinary excretion of As III between Mrp1(ϩ/ϩ) and Mrp1(Ϫ/Ϫ) mice, suggesting that Mrp1 is not critical to urinary excretion of arsenic (28). In sharp contrast to the short exposure times and relatively high doses of arsenic used in these animal studies (28,62,63), human tumor formation is associated with long term exposure to comparatively low doses of arsenic (14).…”
Section: Discussionmentioning
confidence: 99%
“…An independent investigation of Mrp1(Ϫ/Ϫ) mice from the same colony revealed that 1 h after injection of As III there were no differences in urinary excretion of As III between Mrp1(ϩ/ϩ) and Mrp1(Ϫ/Ϫ) mice, suggesting that Mrp1 is not critical to urinary excretion of arsenic (28). In sharp contrast to the short exposure times and relatively high doses of arsenic used in these animal studies (28,62,63), human tumor formation is associated with long term exposure to comparatively low doses of arsenic (14). The high affinity low capacity transport of As(GS) 3 by MRP1 suggests that MRP1 would be better suited to protect tissues from low levels of arsenic and at higher concentrations may be saturated, and other protective mechanisms are required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DMA III -peptide complexes, like the one that can be synthesised from glutathione as DMA III -GS, have not yet been observed in biological samples and are known to be very unstable. [25][26][27] It is, therefore, highly unlikely that DMA III -PC complexes are formed by plants, which might offer a possible explanation for the high TF of DMA V . Only in sulfur-rich plant species of the genus Brassicaceae it has been recently found that DMA V can be complexed by glutathione as a DMAS V -GS complex.…”
Section: Shoot-to-root Tfsmentioning
confidence: 99%